Optimization of Drying Time and Thermal Performance of Solar Dryer for Tekwan Products Based on Energy Balance Analysis - Samosir, Devina Sanchia; Bow, Yohandri; Aswan, Arizal (TECHNO: JURNAL PENELITIAN, 2025)
Energy requirements for production efficiency can be obtained from fossil fuels or renewable energy sources. The traditional drying process in Tekwan production is often inefficient and weather-dependent. Solar-powered drying technology using photovoltaic panels can improve cleanliness, efficiency, and product quality, and is suitable for application in Indonesia. Traditional drying faces challenges in terms of time efficiency and product quality due to weather dependence. This study designed a drying device with tiered racks and an automatic motor for heat distribution. Tests were conducted at 40°C for 1 to 5 hours to analyze moisture content, energy efficiency, and exergy. Results showed a decrease in moisture content from 57.21% to 34% after 5 hours, although it did not meet the SNI 11 standard. The highest thermal efficiency was achieved at 4 hours (84.42%), exergy efficiency was 77.61%, and the lowest exergy loss was 0.520 kJ/mol. Environmental factors, such as humidity and airflow speed, influence performance. Heat loss through convection and radiation remain the main challenges. Design improvements are needed to reduce heat loss and achieve optimal drying.